Upaya Kepala Sekolah dalam Mencegah Perilaku Menyimpang pada Siswa di SMP Negeri 11 Kota Gorontalo - Dea Ananda S. Male; Asmun W. Wantu; Rasid Yunus (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe and analyze the principal's efforts to prevent student deviant behavior at SMP Negeri 11 in Gorontalo City and identify the triggering factors. The study used a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews with the principal as the key informant, and documentation. Data analysis was conducted using the Miles and Huberman interactive model through data reduction, data presentation, and conclusion drawing. The results indicate that the principal implemented a multidimensional approach through discipline enforcement, character development based on religious activities and positive habits, and strengthening collective supervision within the school environment. Student deviant behavior is influenced by internal factors such as low self-control and adolescent psychological conditions, as well as external factors such as family environment, peer influence, and weak school social control. This study concludes that preventing deviant behavior requires a holistic and collaborative approach, with the principal as the primary driver in building a conducive and character-based school culture. The primary contribution of this study is emphasizing the principal's role as an integrator of policies, value reinforcement, and school culture in creating an educational environment that supports the development of positive student behavior.